2012
DOI: 10.1080/09658211.2011.637934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-discrepancy on specificity of autobiographical memory retrieval

Abstract: Research using a cue word paradigm has consistently shown that depression, in both adults and adolescents, is associated with difficulties in retrieving specific autobiographical memories. Inspired by previous work stating that depressed feelings are related to a perceived discrepancy between attributes of the actual and the ideal self, the present study aimed to investigate the hypothesis that cues bringing discrepancies between the actual and ideal selves to the foreground might promote or facilitate the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…All cue words were personal characteristics (e.g., happy, social, friendly; see Schoofs et al, submitted for publication, for an extended description; also see Schoofs, Hermans, & Raes, 2012). Participants are asked to generate specific memories.…”
Section: Autobiographical Memory Test (Amt)mentioning
confidence: 99%
“…All cue words were personal characteristics (e.g., happy, social, friendly; see Schoofs et al, submitted for publication, for an extended description; also see Schoofs, Hermans, & Raes, 2012). Participants are asked to generate specific memories.…”
Section: Autobiographical Memory Test (Amt)mentioning
confidence: 99%
“…While we acknowledge these possibilities, we believe we have neither the data nor a strong enough conceptual basis to speculate how interdependent selfconstrual might have affected different aspects of consistent versus discrepant memories. Just like similar studies comparing conditions/groups in western samples (e.g., Schoofs et al, 2012;Singer et al, 2007), we assumed that these cultural characteristics would affect narratives of self-consistent and self-discrepant memories similarly. Researchers have questioned the validity of Hofstede's dichotomous conceptualisation of individualism versus collectivism (e.g., İmamoğlu, 2003;Kağıtçıbaşı & Berry, 1989;Oyserman et al, 2002) and argued that a given self-construal is unlikely to be true for all members of a given culture to the same degree (İmamoğlu, 2003;Kağıtçıbaşı, 2007;Oyserman et al, 2002).…”
Section: Telling Of Memoriesmentioning
confidence: 98%
“…Of the remaining non-clinical studies, six included school community samples (Brennen et al, 2010;Neshat Doost et al, 2014;Raes et al, 2010;Schoofs, Hermans, & Raes, 2012, study 1 & 2;Smets, Griffith, Wessel, Walschaerts, & Raes, 2013). None of Brennen et al's (2010) sample had a current of previous clinical diagnosis, and Schoofs et al (2012), study 1 and 2 removed participants who met criteria for a current major depressive episode. Neshat Doost et al, 2014, Raes et al (2010 and Smets et al (2013) gave no reference to previous or current clinical psychopathology in their samples.…”
Section: Clinical Status and Participant Selectionmentioning
confidence: 99%
“…Of the four studies with significant effects (Park et al, 2004;Schoofs et al, 2012, study 1 & 2), accounted for symptoms of depression and/or mood. Schoofs et al (2012) entered depression scores as a covariate in their analyses and Park et al (2004) reported that correlations between depression scores and changes in OGM with induced rumination were non-significant. Park et al's (2004) findings suggest that the increase in OGM in the MDD group was not due to changes in mood caused by the rumination induction.…”
Section: Controlling For Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation